Metal‐frame‐integrated eight‐element multiple‐input multiple‐output antenna array in the long term evolution bands 41/42/43 for fifth generation smartphones. Issue 1 (18th November 2018) - Li, Yixin; Sim, Chow‐Yen‐Desmond; Luo, Yong; Yang, Guangli
Abstract : A metal‐frame‐integrated eight‐antenna array operating in the long term evolution bands 41/42/43 (2.496 GHz‐2.69 GHz, 3.4 GHz‐3.8 GHz) for future fifth generation multiple‐input multiple‐output (MIMO) applications in smartphones is presented and discussed. The proposed eight‐antenna MIMO array is formed by integrating four identical building blocks, each of which consists two dual‐mode monopole antenna elements with a neutralization line (NL) embedded in between. Part of the metal frame is exploited to increase the effective resonant length of the monopole antenna. By using the wideband NL, two transmission dips can be generated, and thus an improved isolation (>10 dB) is achieved. The proposed antenna array was simulated and experimentally tested. Good antenna efficiency (>44%) and low envelope correlation coefficient (<0.2) were obtained in the bands of interest. In an 8 × 8 MIMO system with 20 dB signal‐to‐noise ratio, the calculated ergodic channel capacity was as high as 38 bps/Hz in the low band, and 38.3 bps/Hz in the high band. Details of the proposed antenna array are described. The simulated, measured, and calculated results are presented.